Finnish-German young adult's bicultural identity and its realization in Finland - Tommila, Maaria (2015)
Since Germany is one of Finland’s biggest trade partners and at the same time Finland is an emigration country for its young adults, i.e. potential employees, it is important to study the Finnish-German young adults and their cultural identity in Finland. In today’s global world also the Finnish society is developing into a culturally diverse direction which is why different cultural groups and their conditions in Finland should be studied widely. This thesis provides one perspective to this broad discussion.